CD16(+) Monocyte Subset Was Enriched and Functionally Exacerbated in Driving T-Cell Activation and B-Cell Response in Systemic Lupus Erythematosus - Zhu, Huaqun (Front Immunol, 2016)
BACKGROUND: The roles that CD16(+) monocyte subset plays in T-cell activation and B-cell response have not been well studied in systemic lupus erythematosus (SLE). OBJECTIVE: The present study aimed to investigate the distribution of CD16(+) monocyte subsets in SLE and explore their possible roles in T-cell activation and B-cell differentiation. METHODS: The frequencies of monocyte subsets in the peripheral blood of healthy controls (HCs) and patients with SLE were determined by flow cytometry. Monocyte subsets were sorted and cocultured with CD4(+) T cells and CD19(+) B cells. Then, T and B cells were collected for different subset detection, while the supernatants were collected for immunoglobulin G, IgA, and IgM or interferon-γ and interleukin-17A detection by enzyme-linked immunosorbent assay. RESULTS: Our results showed that CD16(+) monocytes exhibited a proinflammatory phenotype with elevated CD80, CD86, HLA-DR, and CX3CR1 expression on the cell surface. It’s further demonstrated that CD16(+) monocytes from patients and HCs shared different cell-surface marker profiles. The CD16(+) subset was enriched in SLE and had an exacerbated capacity to promote CD4(+) T cell polarization into a Th17 phenotype. Also, CD16(+) monocytes had enhanced impacts on CD19(+) B cells to differentiate into plasma B cells and regulatory B cells with more Ig production. CONCLUSION: This study demonstrated that CD16(+) monocytes, characterized by different cell-surface marker profiles, were enriched and played a critical role in driving the pathogenic T- and B-cell responses in patients with SLE.